2013
DOI: 10.1590/s0100-06832013000200024
|View full text |Cite
|
Sign up to set email alerts
|

Erosividade das chuvas associada a períodos de retorno e probabilidade de ocorrência no estado do Rio de Janeiro

Abstract: RESUMOO conhecimento da erosividade das chuvas associada à probabilidade de ocorrência e ao período de retorno pode contribuir para o planejamento conservacionista de uma região, em médio e longo prazo. A fim de gerar informações para melhor utilizar modelos e controle da erosão, dados de chuvas de 30 séries pluviográficas e pluviométricas, abrangendo 25 municípios, entre 1933 e 2006, foram estudados quanto à adequação das séries e do cálculo da probabilidade de ocorrência teórica (P) e período de retorno (T) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
1
4
0
5
Order By: Relevance
“…In the tropics, precipitation is the most influential climatic factor for soil erosion due to the volume and time and space distribution (Machado et al, 2013). Martins et al (2010a), in a study in Aracruz, state of Espírito Santo (a region close to the present study area), observed a variation between years from 4,536 to 17,056 MJ mm ha -1 h -1 year -1 , reinforcing the knowledge of the great variability of the precipitation behavior in the region.…”
Section: Resultssupporting
confidence: 73%
“…In the tropics, precipitation is the most influential climatic factor for soil erosion due to the volume and time and space distribution (Machado et al, 2013). Martins et al (2010a), in a study in Aracruz, state of Espírito Santo (a region close to the present study area), observed a variation between years from 4,536 to 17,056 MJ mm ha -1 h -1 year -1 , reinforcing the knowledge of the great variability of the precipitation behavior in the region.…”
Section: Resultssupporting
confidence: 73%
“…According to Machado et al (2013), the mean annual erosivity in the region of Seropédica-RJ is 5,960.4 MJ mm ha -1 h -1 , with maximum of 9,792.9 MJ mm ha -1 h -1 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, higher erosive potential is expected in this group because of the rainfall events with physical characteristics of high rainfall depth, high I 30 , and long duration, because the standardized canonical coefficient (SCC) and the correlation coefficient (r) of these characteristics were positive. Except for the Campos station, the highest scores in the delayed pattern were obtained for stations located in the regions South Fluminense, Central Fluminense, and Metropolitan, which had the highest monthly and annual mean values of rainfall (André et al, 2008;Brito et al, 2016) and the highest values of rainfall erosivity in the state (Montebeller et al, 2007;Machado et al, 2013). These results are highly influenced by the topography and higher air humidity coming from the ocean in the southeast direction (André et al, 2008).…”
Section: Resultsmentioning
confidence: 95%